Impact of COVID-19 Lock down on Farmers of Nalgonda District, Telangana State - Pallavi Surapaka; M. A. Aariff Khan, Himabindu Tanguturi, Shankar Marlabeedu, Bharath Tejavath, Shankaraiah Mekala (Indian Journal of Extension Education, 2022)
COVID-19 is the greatest humatarian challenge the world has faced and effected agriculture and allied sectors. The study was carried out to know the Impact of COVID-19 lockdown on farmers and allied sectors in terms of Social, Economic, Psychological, Situational parameters. The Google form Questionnaire was used to collect the information from randomly selected 120 farmers of Nalgonda district. It was observed that non-celebration of important events (98.33%), high labour wages coupled with low market price of horticulture produce drastically affected the farmers returns (85%) and majority of farmers had fear of increasing debts due to low market price of produce (80%) and nonavailability of agriculture labour for performing field operations (70%) etc. were the major Social, Economic, Psychological and Situational effects on farmers respectively. In case of impact on agriculture and allied sectors, despite the problem few of the farmers adopted alternative mechanism of door-to-door supply of fruits and vegetables, few of the villagers aggregated their vegetable produce and marketed to nearby local towns and cities. Majority of the farmers found that technology-driven advisories issued by KVK, Kampasagar, Nalgonda District has helped the farmers to tackle their problems timely.